PERLINDUNGAN KONSUMEN TERHADAP MENINGKATNYA PENIPUAN PRODUK YANG DIPERJUALBELIKAN SECARA ONLINE - Fitri Fitri (Yayasan Merassa Indonesia Publikasi, 2024)
Use of electronic media to function as computerized information when making agreements, organizations that carry out their activities using electronic me- dia, for example the web, will see an impact on their exhibitions. However, considering that the agreement is made online does not mean there are no problems. This problem arises as a result of the increasingly widespread vio- lations that utilize the internet, in particular the widespread misrepresentation online, especially in online conversations. The enactment of Law Number 2 shows the efforts made by public authorities to protect consumers. 8 of 1999, which regulates customer guarantees. where consumer responsibilities and rights have been regulated. In addition, vendors have privileges and commit- ments. Therefore, the author's proposed research subject is